New pedagogical approaches in game enhanced learning curriculum integration - Freitas, Sara de; Ott, Michela; Popescu, Maria Magdalena; Stanescu, Ioana (Information Science Reference, 2013)
"This book addresses the major challenges associated with adopting digital games into a standard curriculum, providing fresh perspectives from current practitioners in the education field" - Provided by publisher
Includes bibliographical references and index
Keywords: E-Learning; Computerspiel; Edutainment; Aufsatzsammlung